Prova Brasil : uma reflexão sobre a concepção de letramento - Casaril, Marina (2014)
Under the light of documentary research (GIL, 2002), the current study reflects on the conception of literacy in Prova Brasil, one evaluative national exam of major importance in its country. Considering the great myriad of social practices which Brazilian students from the 9th grade engage in, we ponder: does the current exam model propose an evaluation that privileges such practices? Which literacy model does the exam adopt? To puzzle out solutions, we analyzed a 9th grade exam model of the Prova Brasil, made available by Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira (INEP). The theoretical framework that guided our study was grounded in the New Literacy Studies. This approach advocates that literacy is to be seen as observable social practices from which subjects in literacy programs can be assisted with in order to empower themselves from the most relevant literary practices in their context (STREET, 2014), instead of seeing literacy in terms of social impact on education, literacy and politics. From this perspective, we observed the conception of literacy presented in the Brazil exam by accounting for the recurrence of the selected genres, as well as for the interaction patterns predicted by the exam. As regards the results, we perceived that the choice for discourse genres as well as the choice for their support and, many times, the choice for the set of themes privileged literacy of specific groups. In addition, as concerns reading, the elaboration of questions, in their majority, does not foresee the social practices that are constituted by these genres, presenting few elements that can assist students to recognize the genre and the practice which is represented. These questions also focused excessively on descriptors and repeated them, in a few cases. Therefore, it is possible to state that the literacy model presented in the exam is the autonomous model still. An exam model that is applied throughout the entire country may not be sufficient for evaluating reading, given the fact that practices vary according to each community and there is no apparent way of imposing an exam "pattern" that can assess students the same way. After all, each human relation with literacy in Brazilian Portuguese is constituted locally, socially, culturally and ideologically.